(untitled) (Hekima Review, 2010)
Political Participation in Zimbabwe is a lucid, impressive and latest book edited by David Kaulemu. It is based on research and advocacy on the character and levels of political participation in Zimbabwe. It is a twenty eight articled-book written on the levels and nature of political participation on Zimbabwe. In its 292 pages, the wonderful book raises questions, assumptions, propositions, opportunities, challenges and solutions to the political participation in Zimbabwe.